Desquamative interstitial pneumonia in a child related to cigarette smoke. Issue 3 (17th June 2013) - Ischander, Mariam; Fan, Leland L.; Farahmand, Vanda; Langston, Claire; Yazdani, Shahram
Summary An 8‐year‐old white male was referred to our clinic for a 1‐year history of decreased appetite and no weight gain. His entire workup failed to demonstrate cystic fibrosis, or any infectious or immune‐related diseases. Chest imaging and clinical picture suggested parenchymal lung disease. Histopathology examination of the video‐assisted thoracoscopic biopsy of his lungs showed a desquamative interstitial pneumonia (DIP)‐like pattern that resembled that of adult smokers with the same disease. Genes for surfactant proteins B and C and the transporter ABCA3 were all negative. Furthermore, lack of any genetic disorder for surfactant proteins, along with his history of heavy exposure to 10 pack‐years of indoor secondhand smoke suggests that this child's DIP is due to secondhand cigarette exposure. He had nearly complete resolution of his symptoms after a year of treatments with pulse steroid and hydroxycholoroquine. To the best of our knowledge this is the first case of cigarette smoke‐related DIP reported in a child. Pediatr Pulmonol. 2014; 49:E56–E58. © 2013 Wiley Periodicals, Inc.